Archives in Strategic Decision-Making (A Case Study at the Faculty of Communication Science Universitas Padjadjaran) - Encang Saepudin; Fadhilah Muhammad; Sukaesih Sukaesih (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
Archives could be as data as a basis for consideration, knowledge, thoughts, and decision making. This study aims to determine the use of archives in strategic decision making. This study uses a qualitative method with a case study approach. The data were obtained through interviews with 5 persons (3 faculty leaders and 2 archivists). The data were also obtained through discussion, observation, and literature study. Validity and reliability tests through the process of triangulation of data and triangulation of sources. The descriptive data analysis through the stages of data reduction, data presentation, and drawing conclusions. The study found that there were four factors that influenced the use of archives in the decision-making process by the leaders which were the type of decision making, the basis for decision making, the existence of regulations, and organizational culture. The type of decision making used is unprogrammed decisions because it has new and unstructured characteristics. The basis for decision making is rational. This means that decision making is based on certain things. There are regulations that contradict one rule with another. And the prevailing culture which makes difficult for leaders to to carry out change management. As conclusion, the archive has been used as a basis for decision making.